3D modelling of the Excavation Damaged Zone using a Marked Point Process technique. (March 2019) - Alcolea Rodríguez, Andrés; Kuhlmann, Uli; Marschall, Paul
Abstract: The Excavation Damage Zone (EDZ) is a key aspect in the assessment of engineering feasibility and long-term safety of deep geological repositories for radioactive waste. The EDZ represents a possible release path for radionuclides dissolved in the porewater and for gases from corrosion and degradation processes which needs to be addressed quantitatively in Safety Assessment (SA). The EDZ is often represented by a discrete fracture network, whose complexity precludes its implementation in conventional SA models. To overcome this problem, two-dimensional abstraction methodologies have been developed that replace the complex geometry of the discrete fracture network by a hydraulically equivalent continuum model. Although such simple 2D models are amenable to SA modelling, they cannot capture the inherent three-dimensional and stochastic nature of the phenomena associated with the EDZ. In this paper we present a methodology based on Marked Point Processes to infer 3D stochastic continuum models of the EDZ from 2D discrete characterizations of the fracture network. The methodology is illustrated with the calibration of a multi-rate injection experiment in Mont Terri (Switzerland). Highlights: An efficient approach for the 3D stochastic modelling of the Excavation Damaged Zone is proposed. The approach relies on 2D geomechanical simulations as training data sets. Two applications, including the calibration of a complex hydraulic test in Mont Terri (Switzerland), are presented.